Training Programs and Developmental Opportunities of Human Resource Practices with Job Performance - Desa, Nasina Mat; Asaari, Muhammad Hasmi Abu Hassan (AESS Publications, 2019)
This study examines the association between human resource practices, namely training programs and developmental opportunities; toward job performance, namely task performance and contextual performance. Malaysian engineers in the manufacturing sector of electrical and electronics in the Bayan Lepas Free Trade Zone, Penang were studied. Self-Administered questionnaires were distributed through several human resource managers and distributed to their engineers. The research tools were adapted and adopted from Conway and Monks on the training programs, Allen et al. (2003) on the developmental opportunities, Williams and Anderson on the task performance, and Hochwarter et al. (2003) on the contextual performance. This study employed demographic analysis, reliability analysis, correlations analysis, and regression analysis. As results, this study revealed that training programs of human resource practices among engineers had no impact on task performance and contextual performance. On the other hand, engineers indicated that developmental opportunities of human resource practices in their organizations had an impact on task performance and contextual performance.